2019
DOI: 10.1109/access.2019.2899367
|View full text |Cite
|
Sign up to set email alerts
|

Face Recognition Systems Under Morphing Attacks: A Survey

Abstract: Recently, researchers found that the intended generalizability of (deep) face recognition systems increases their vulnerability against attacks. In particular, the attacks based on morphed face images pose a severe security risk to face recognition systems. In the last few years, the topic of (face) image morphing and automated morphing attack detection has sparked the interest of several research laboratories working in the field of biometrics and many different approaches have been published. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(159 citation statements)
references
References 106 publications
1
158
0
Order By: Relevance
“…All of them provide a high-quality performance with morphed images, but it should be noticed that researchers have to perform manual manipulation and generate a large enough number of images to achieve an adequate corpus for their research works. The well-known algorithm [22], [23] used in the literature is adapted to the studied problem and explained below. a) Given two pictures (see Figure 1(a)), 76 reference points are located in each one.…”
Section: A Morphing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them provide a high-quality performance with morphed images, but it should be noticed that researchers have to perform manual manipulation and generate a large enough number of images to achieve an adequate corpus for their research works. The well-known algorithm [22], [23] used in the literature is adapted to the studied problem and explained below. a) Given two pictures (see Figure 1(a)), 76 reference points are located in each one.…”
Section: A Morphing Processmentioning
confidence: 99%
“…In recent years, the wide use of ABC systems in airports has increased the attention and the study of the possible multiple menaces (e.g., presentation attack) as explained by the European Border and Coast Guard Agency (FRON-TEX) [17], [18]. These attacks incentivize the proliferation of algorithms about presentation attack detection (PAD) [19]- [21] and especially morphing attack detection (MAD) [13], [22] because it is a difficult paradigm to be detected.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, face images used for the ePassport issuance are provided by the applicant. Based on this security gap in the process, the vulnerability of face recognition systems to so-called morphing attacks has been recently exposed [71], [72]. Similarly, facial retouching could be applied, which could significantly degrade the performance of a face recognition system, e.g., at automated border controls.…”
Section: Facial Retouchingmentioning
confidence: 99%
“…Benchmarks of state-of-the-art (commercial and open-source) face recognition systems are required to further investigate this hypothesis. However, recently researchers found that the improved generalizability of deep face recognition systems increases their vulnerability against attacks, e.g., spoofing attacks (also referred to as presentation attacks) [81] or face morphing attacks [71], [72]. Security aspects Facial beautification can have security implications on face recognition systems.…”
Section: Issues and Challengesmentioning
confidence: 99%
“…Recently, the spectral analysis of Photo Response Non-Uniformity (PRNU) has been em-ployed [8] [22], to analyse modifications caused by the morphing procedure. For a quick overview of the existing state of the art based on morph attack detection are presented in [23].…”
Section: Related Workmentioning
confidence: 99%